2024
DOI: 10.21608/ejoh.2023.214545.1250
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Propagation of New Almond × Peach Hybrids by Hard Wood Cuttings

Ghada Soliman

Abstract: T HIS experiment was conducted on 2019 & 2020 to study the effect of root hormones within two different water irrigation pH. on five new almond ×peach hybrids that are nematode resistance and salt tolerance. Rootstock trees are nine years old grown in Horticulture Research Institute, A.R.C. and received the same recommended horticultural practices. This experiment consisted of eight treatments using Indole Butyric Acid (IBA) at concentrations of 1000&2000ppm with or without 500ppm Naphthalene Acetic Acid (NAA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…The promotive effect of auxins in this regard may result from the enhancement of hydrolysis activity associated with increases in the formation of highly soluble carbohydrates and leads to the increment in root formation and better rooting, which leads to good shoot growth and good internal elements. This is due to an increase in hormones and carbohydrates in root cells, increased nutrient uptake, increased translocation of metabolites to the growing apices, enhanced callus formation, and differentiation of vascular tissues, it also promotes the differentiation of cambial initials into root primordia, and increases the mobilization of reserve food material to sites of root initiation (Soliman 2024). The same results were recorded by Abuazizah et al, (2023) and Brighenti et al, (2023) on grapes rooting woody cuttings.…”
Section: Effect Of Growing Mediasupporting
confidence: 73%
See 1 more Smart Citation
“…The promotive effect of auxins in this regard may result from the enhancement of hydrolysis activity associated with increases in the formation of highly soluble carbohydrates and leads to the increment in root formation and better rooting, which leads to good shoot growth and good internal elements. This is due to an increase in hormones and carbohydrates in root cells, increased nutrient uptake, increased translocation of metabolites to the growing apices, enhanced callus formation, and differentiation of vascular tissues, it also promotes the differentiation of cambial initials into root primordia, and increases the mobilization of reserve food material to sites of root initiation (Soliman 2024). The same results were recorded by Abuazizah et al, (2023) and Brighenti et al, (2023) on grapes rooting woody cuttings.…”
Section: Effect Of Growing Mediasupporting
confidence: 73%
“…In terms of the fresh and dry weight of the leaves (g/cutting), the cuttings were grown in peatmoss and pre-planting dipped in 2000 mg/l IBA was excelled compared to the other treatments, as the maximum average of fresh and dry weight of leaves 22.23 g/cutting, and 4.79 g/cutting, respectively. Soliman (2024) reported that IBA usage enhanced the formation of roots and increased rooting percentage in Almond, and Peach wood cuttings. Also, Kaviani et al, (2023) confirmed that plant hormones such as IBA and NAA) had the greatest effect on most of the pear cuttings' growth measurements (rooting percentage, root number, root length, leaf number, as well as fresh and dry weights.…”
Section: Effect Of Growing Mediamentioning
confidence: 99%